Association Between the Expression of MicroRNA-125b and Survival in Patients With Acute Coronary Syndrome and Coronary Multivessel Disease - Gager, Gloria M.; Eyileten, Ceren; Postula, Marek; Gasecka, Aleksandra; Jarosz-Popek, Joanna; Gelbenegger, Georg; Jilma, Bernd; Lang, Irene; Siller-Matula, Jolanta (Frontiers in Cardiovascular Medicine, 2022)
Background MicroRNAs (miRNA, miR) have an undeniable physiological and pathophysiological significance and act as promising novel biomarkers. The aim of the study was to investigate blood-derived miRNAs and their association with long-term all-cause mortality in patients with multivessel disease (MVD) suffering from acute coronary syndrome (ACS). Materials and Methods This study was an observational prospective study, which included 90 patients with MVD and ACS. Expression of miR-125a, miR-125b, and miR-223 was analysed by polymerase chain reaction (PCR). Patients were followed-up for a median of 7.5 years. All-cause mortality was considered as the primary endpoint. Adjusted Cox-regression analysis was performed for prediction of events. Results Elevated expression of miR-125b (>4.6) at the time-point of ACS was associated with increased long-term all-cause mortality (adjusted [adj.] hazard ratio [HR] = 11.26, 95% confidence interval [95% CI]: 1.15–110.38; p = 0.038). The receiver operating characteristic (ROC) analysis showed a satisfactory c-statistics for miR-125b for the prediction of long-term all-cause mortality (area under the curve [AUC] = 0.76, 95% CI: 0.61–0.91; p = 0.034; the negative predictive value of 98%). Kaplan–Meier time to event analysis confirmed an early separation of the survival curves between patients with high vs low expression of miR-125b (p = 0.003). An increased expression of miR-125a and miR-223 was found in patients with non-ST-segment elevation ACS (NSTE-ACS) as compared to those with ST-segment elevation myocardial infarction (STEMI) (p = 0.043 and p = 0.049, respectively) with no difference in the expression of miR-125b between the type of ACS. Conclusion In this hypothesis generating study, lower values of miR-125b were related to improved long-term survival in patients with ACS and MVD. Larger studies are needed to investigate whether miR-125b can be used as a suitable predictor for long-term all-cause mortality.